Epidemiological pattern of rape cases managed at a regional hospital in South Africa - Chika K. Egenasi; Mathew A. Benedict; Anthonio O. Adefuye; Lynda U. Madu (AOSIS, 2024)
Background: South Africa has one of the highest incidences of rape globally. Understanding the epidemiological pattern of rape is needed to inform the design of effective intervention programmes for rape prevention and management of alleged rape cases. Aims: To investigate important epidemiological patterns associated with rape in Kimberly, Northern Cape Province, South Africa. Setting: The Robert Mangaliso Sobukwe Hospital (RMSH) forensic unit. Methods: A descriptive, retrospective cross-sectional clinical audit of rape cases. Results: The majority (93.3%) of the alleged rape victims were women, with a mean age (SD) of 21.6 years (11.3); the male population made up 6.7% of the cases, with a mean age (SD) of 10.5 years (6.9). The highest incidence of alleged rape in the male population was seen in the age group ≤ 16 years (81.8%) and for women 17-30 years (50.3%). Most of the incidents occurred at the perpetrators' homes (42.7%); on the days Fridays (14.6%), Saturdays (29.9%) and Sundays (23.2%); at night up to midnight 20:00-23:59 (32.9%) (p = 0.01) and involved threats of violence (55.5%). The majority (56.0%) of the perpetrators were known to the victims. Conclusion: Important information about the victims and circumstances in which rape occurs as reported herein can be used to inform the design of effective intervention programmes for sexual crime prevention and management in Kimberly, South Africa. Contribution: This study helped to advance knowledge and understanding of the epidemiological pattern associated with rape in Kimberley, Northern Cape Province of South Africa.